Pengaruh Pembelajaran Matematika Dengan Menggunakan Model Reciprocal Teaching Terhadap Kemampuan Komunikasi Matematika SMP AL-ISLAM 1 Surakarta Tahun Pelajaran 2015/2016 - AZIZATUL KHUMAIRA, RETNO (2016)
This thesis entitled "The Effect of Learning Mathematical Model Using Reciprocal Teaching Communication Skills Math Junior Against Al-Islam 1 Surakarta academic year 2015/2016" quite fathomable this study whether there is influence Reciprocal Teaching models for mathematical communication skills SMP Al-Islam 1 Surakarta. The purpose of this study was to determine the effect of the model of Reciprocal Teaching communication skills mate, atika SMP Al-Islam 1 Surakarta. This type of research is experimental. The population in this study were all students in grade VII.Teknik data collection techniques used are one way ANOVA. Sampling in this study dlakukan by cluster random sampling. Berdasarkanhasil empirically that α = 0.05 was obtained T count = 1,446 and Ttabel = 1,960.hal This suggests that there are significant Reciprocal Teaching models for mathematical communication skills junior high school students of Al-Islam 1 Surakarta Pelajarn year 2015/2016.